What Happened in Northern Norway? - A comparative and quantitative analysis of political and demographic development in Northern Norway from 1950 to 2015 - Stein, Jonas (Territory, Politics, Governance, 2019)
The thesis What Happened in Northern Norway? is a quantitative analysis of various aspects of the political and demographic development in Northern Norway from 1950 to today. The theories of Ottar Brox and in his seminal work Hva skjer i Nord-Norge? (What Is Happening in Northern Norway?), have influenced regional and national actors in their understanding of the region and their policy development. This thesis aims to analyze what actually happened in Northern Norway in the years following Brox’s work by using a different theoretical framework for the center‒periphery relationship, one developed by another social scientist with roots in Northern Norway, Stein Rokkan, and by applying quantitative methodology. The first paper, “The Striking Similarities between Northern Norway and Northern Sweden,” published in Arctic Review on Law and Politics (2019), uses a comparative perspective to find a very similar pattern of demographic development in municipalities in Northern Norway and Northern Sweden, especially from 1975 to 2015, despite important differences in regional policies applied in the two countries. In the second paper, “The Centre‒Periphery Dimension and Trust in Politicians: The Case of Norway,” published in Territory, Politics, Governance (2019), Northern Norway serves as a case for exploring if there is a spatial dimension in trust in politicians that goes beyond the urban‒rural dimension. The results produced when using the Rokkanian framework reveal lower trust in national and local politicians in Northern Norway than elsewhere in the country, despite controlling for performance, cultural, political, and socio-economic variables. The paper also shows how distance from the capital could replace the dummy variable Northern Norway and, hence, has relevance for trust studies in other countries. The third paper, “The Local Impact of Increased Numbers of State Employees on Start-ups in Norway,” published in Norwegian Journal of Geography (2019), examines the effect of regional policies particularly ...